PERLINDUNGAN HAK ATAS PENGUASAAN TANAH TRANSMIGRASI YANG DI TERLANTARKAN DAN DI TINGGALKAN OLEH TRANSMIGRAN DI LAHAN USAHA II UPT SEUNAAM IV PROVINSI ACEH - IRWAN HARYO WARDANI (PREMISE LAW JURNAL, 2016)
The conclusion of this thesis is that the legal consequence of the status of the land that is neglected and abandoned by the transmigrants areas in UPT Seunaam IV is that the SKBT (Certificate of Land Division) is annulled for the transmigrants who have neglected and abandoned the land. The legal status on the possession of transmigration land by the people who are not the participants of the transmigration is that they can apply for it to the Governor, First Level Regional Head i.e the related Head Office of Agricultural Office so that they are entitled as land ownership right as long as they fulfill the terms and condition applied by the Director General of Agriculture and Transmigration. The authorized office’s effort is to overcome the provision of right on the transmigration land is that the Regional Government of Nagan Raya District and the Government of Aceh Province together with the Central Government, namely under the Ministry of Agriculture and Space Management/National Land Board and Ministry of Suburban Development and Transmigration have the policy, namely by participating the people who are not the participants of transmigration to be the local transmigration participants. By becoming the local transmigration participants, the people who are not participants of transmigration can get the land ownership right. Keywords : Protection of Possession, Transmigration Land, Seunaam IV